Assessing the quality of the undergraduate curriculum in two library and information science (LIS) schools in Nigeria/ Bappah Magaji Abubakar and Basri Hassan - Abubakar, Bappah Magaji; Hassan, Basri (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Changes in the LIS curriculum especially in this digital age has become a constant phenomenon globally. However, in the developing countries like Nigeria, it has been relatively very slow due to the low level of infrastructural development. Consequently, there is a need for the blending of traditional and modern courses in the curricula of the LIS schools in the country. This study investigates the opinions of academic staff in two (2) LIS schools in Nigeria regarding the quality of the undergraduate LIS curricula and the roles played by the employers of the LIS graduates in curricula matters. A descriptive survey research technique was used in the study, with the data collected through the use of questionnaire. The findings reveal that respondents indicated that the curricula of their LIS schools contained minimal Information Technology (IT} courses. Majority of them indicated that they were involved in the curriculum review process in their respective LIS schools. However, the study also revealed that the employers of the LIS graduates were not involved in the curriculum review process of their employees' LIS schools. Recommendations were made based on the results of this study.